2018
DOI: 10.4102/ojvr.v85i1.1568
|View full text |Cite
|
Sign up to set email alerts
|

Detection of virulence factors of South African Lactococcus garvieae isolated from rainbow trout, Oncorhynchus mykiss (Walbaum)

Abstract: Lactococcus garvieae is a Gram-positive bacterium that causes mortalities in freshwater and marine fish worldwide and therefore results in severe economic losses in the aquaculture industry. Apart from the apparent integral role of the exopolysaccharide (EPS) capsule in pathogenesis, factors associated with virulence of this bacterium are poorly understood. However, recent studies have indicated that the ability of L. garvieae to cause disease does not depend on the presence of the EPS capsule. Lack of knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Previously, it was believed that pathogenic L. garvieae isolates possessed capsules (KG−/agglutinating), whereas non‐capsulated isolates (KG+/non‐agglutinating) were non‐pathogenic (Barnes & Ellis, 2004; Ooyama et al, 2006). However, recent isolates have proven this assumption incorrect, as non‐capsulated strains have also been found to be virulent in fish (Meyburgh et al, 2018; Shahi et al, 2018). Multiplex PCR confirmed the absence of a capsule gene cluster.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was believed that pathogenic L. garvieae isolates possessed capsules (KG−/agglutinating), whereas non‐capsulated isolates (KG+/non‐agglutinating) were non‐pathogenic (Barnes & Ellis, 2004; Ooyama et al, 2006). However, recent isolates have proven this assumption incorrect, as non‐capsulated strains have also been found to be virulent in fish (Meyburgh et al, 2018; Shahi et al, 2018). Multiplex PCR confirmed the absence of a capsule gene cluster.…”
Section: Discussionmentioning
confidence: 99%
“…This bacterium was resistant to multiple antibiotics. Eiji et al, (68) reported virulence genes in L. garvieae from different sources using comparative genomic analysis and recently, this bacterium isolated from diseased rainbow trout was reported to have carried important virulence genes such as haemolysins 1,2,3, NADH oxidase, phosphoglucomutase, adhesins, superoxide dismutase, enolase, among others (69,70).…”
Section: Lactococcusmentioning
confidence: 99%
“…Bacterial pathogenicity is primarily determined by virulence genes: some facilitate adhesion and invasion, whereas antimicrobial resistance (AMR), particularly multidrug resistance, is an important threat to public health ( 21 ). For L. garvieae , several virulence genes and antimicrobial resistance genes were identified using traditional methods (e.g., PCR) targeted at specific virulence genes ( 22 24 ). However, a comprehensive profiling of its virulence and antimicrobial resistance genes is lacking.…”
Section: Introductionmentioning
confidence: 99%